LIBERASI TEOLOGI DI IRAN PASCA-REVOLUSI: Telisik Pemikiran Abdul Karim Soroush - Fahmy Farid Purnama (Fakultas Ushuluddin dan Humaniora, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2016)
Abstract: This paper will discuss the identity struggle and discourse of thought in the Islamic world, especially in the Islamic civilization and culture of Iran. That is, by trying to explain various religio-philosophical discourse presented by Soroush to restore Iranian civilization from an identity crisis, psychological deterioration, to the ontological dislocation that have obscured the authenticity of existential society. This paper will also explain why Soroush calls for new directions in theology and Islamic political discourse, particularly in Iran, which is supported by various philosophical discourse. By involving the philosophy of science (epistemology) in understanding human religiosity, Soroush philosophical thought also necessitates a new perspective of looking at reality, both the reality of individual, social, or global.Abstrak: Tulisan ini akan mengurai pergulatan identitas dan wacana pemikiran di dunia Islam, khususnya di kancah peradaban dan kebudayaan Iran. Yaitu dengan berusaha menjelaskan pelbagai wacana filsafat-keagamaan yang diketengahkan Soroush untuk memulihkan peradaban Iran dari krisis identitas, keterpurukan psikologis, hingga dislokasi ontologis yang telah mengaburkan otentisitas eksistensial masyarakatnya. Tulisan ini juga akan menjelaskan mengapa Soroush menghendaki adanya arah baru dalam diskursus teologi dan politik Islam, khususnya di Iran, yang ditopang oleh pelbagai wacana filosofis. Dengan melibatkan filsafat ilmu (epistemologi) dalam memahami religiusitas manusia, pembacaan Soroush juga meniscayakan suatu perspektif baru dalam memandang realitas, baik realitas individual, sosial, maupun global.